1992
DOI: 10.1152/ajpheart.1992.262.5.h1611
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a kynurenate-insensitive glutamate receptor in nucleus tractus solitarii

Abstract: Previous studies have shown that pharmacological blockade of ionotropic excitatory amino acid (EAA) receptors in the nucleus tractus solitarii (NTS) with kynurenate (Kyn) abolishes baroreceptor reflexes but fails to affect cardiovascular responses evoked by microinjections of L-glutamate (Glu) into the NTS. These observations have raised doubts as to whether Glu is a neurotransmitter of baroreceptor information in the NTS because the pharmacological actions of exogenously administered Glu are not identical to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
36
0
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 19 publications
7
36
0
1
Order By: Relevance
“…On the other hand, (1S,3R)-ACPD injected in the CVLM produced dose-dependent decreases in blood pressure and SNA that are characteristic of stimulation of sympathoinhibitory neurons of this region. These observations bear a striking resemblance to the findings of Pawloski-Dahm and Gordon, 9 who showed that (rans-ACPD injected in the NTS evoked depressor responses. Although our data represent the first observations in rats that mGluR in the ventrolateral medulla may participate in cardiovascular regulation, our findings are in agreement with the preliminary report of McManigle et al 19 that trans-ACPD injected in the CVLM of cats decreased blood pressure and HR.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…On the other hand, (1S,3R)-ACPD injected in the CVLM produced dose-dependent decreases in blood pressure and SNA that are characteristic of stimulation of sympathoinhibitory neurons of this region. These observations bear a striking resemblance to the findings of Pawloski-Dahm and Gordon, 9 who showed that (rans-ACPD injected in the NTS evoked depressor responses. Although our data represent the first observations in rats that mGluR in the ventrolateral medulla may participate in cardiovascular regulation, our findings are in agreement with the preliminary report of McManigle et al 19 that trans-ACPD injected in the CVLM of cats decreased blood pressure and HR.…”
Section: Discussionsupporting
confidence: 85%
“…4 - 5 The pharmacological and functional characteristics of mGluR have been disclosed by using a selective mGluR agonist, (±)-l-aminocyclopentane-fran.s-l,3-dicarboxylic acid (frans-ACPD*). 6 - 8 Recently, Pawloski-Dahm and Gordon 9 showed that activation of mGluR by trans-ACPD injected in the nucleus tractus solitarii (NTS) evoked cardiovascular effects that were similar to those produced by Glu.…”
mentioning
confidence: 99%
“…A possible explanation is that the increase in AP was presumably due to vasoconstriction in mesenteric arteries [4,13] but also partly in consequence of a rise in cardiac output (tachycardia). The increase in AP baseline following suramin or kynurenate microinjected into the NTS was similar to reports in previous studies [35][36][37][38]. Although the cardiovascular changes reverted to resting values prior to injections after ∼20-30 min, the receptors remained blocked by the antagonists that were tested by respective agonists.…”
Section: Hindlimb Vasodilation In Alerting-defense Responses Is Mediasupporting
confidence: 89%
“…Perhaps compensatory mechanisms in the contralateral NTS prevent the baseline BP from rising. Consistent with this explanation are the reports that bilateral blockade of glutamate receptors in the NTS are necessary to increase the baseline BP (24). Furthermore, blockade of ionotropic as well as metabotropic glutamate receptors in the NTS may be necessary to elevate baseline BP (11).…”
Section: Discussionmentioning
confidence: 58%